KOMODIFIKASI ANAK MUDA DALAM DEVELOPMENT BASKETBALL LEAGUE DI HALAMAN DETEKSI SURAT KABAR JAWA POS - Hadi Sampurna (Faculty of Humanities, Jember University, 2015)
The newspaper is as an institution which plays an important information provider in the construction of the structure of government, politics, law, economics, education, and culture.It serves commodification measures to safeguard the existence and to maximize profits. The research in the study of culture and media frames uses commodification theory and applies critical discourse analysis of Norman Fairclough. The study found that Jawa Pos has done process of commodification of young people in the newspaper business. This is done to young children who have great potentials for business development. The commodification was carried out through page “Detection” which has as one of its programs, Development Basketball League competition. Jawa Pos run a process of hegemony on younger children sooftly by introducing, shaping, and instilling a compelling discourse and encouraging their participation. It increases the image and circulation of Jawa Pos which maximize its finacial benefit.Keywords: young people, commodification, modern, Americanized